ANALYSIS OF CAFFEINE LEVELS IN KOPI KHOP BEVERAGE WITH SPECTROSCOPIC METHOD - Sabarni Sabarni; Nurhayati Nurhayati (Lantanida Journal, 2018)
In addition of being dubbed as the city of "Serambi Mekah", Aceh is also famous as the city of "Thousand Coffee Shops". One of coffee dish that attracts consumers' is khop coffee (read: kopi khop) because it is served with a glass dish upside down. The khop coffee, a typical coffee drink from Meulaboh, West Aceh Regency, is served by reversing the glass that has been filled with coarse coffee powder on top of the pan. Therefore, it is deemed necessary to conduct a special study on the analysis of unique taste-determining compounds in khop coffee to elevate the local wisdom of the Acehnese to the scientific region. The aim of this study was to determine the concentration of caffeine compounds of khop coffee due to the modification of coffee powder diameter by using the thin layer chromatography (TLC) method and UV-Vis spectrophotometry. This study used four types of samples with diameter variations coffee, namely original, fine, medium, and coarse. The four samples were extracted with boiling hot water according to the same conditions when the bartender served it (90 °C) followed by liquid-liquid extraction using chloroform solvent. Dry extract was analyzed by using TLC followed by a UV-Vis spectrometer. The results showed that the concentrations of original, fine, medium, and coarse coffee were respectively 57.85%; 17.61%; 1.29%; and 0.83%.